2001
DOI: 10.1177/070674370104600909
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Borderline Personality Disorder in a Sample of French High School Students

Abstract: Ob jec tive: To es ti mate the fre quency of bor der line per son al ity dis or der (BPD) in French high school stu dents. Method: A ran dom sam ple of high school stu dents (n=1363) rang ing in age from Con clu sion: This study found a high fre quency of BPD in French ado les cents, which adds to ques tions re gard ing the va lid ity of di ag nos ing this dis or der in ado les cents.(Can J Psy chia try 2001;46:847-849) Key Words: adolescence, borderline personality disorder, frequency S ome stud ies have sug … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
31
0
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(41 citation statements)
references
References 12 publications
(4 reference statements)
5
31
0
5
Order By: Relevance
“…These elements are reminiscent of those defined as criteria for certain personality disorders (such as borderline or antisocial personality disorder) in the 4th edition of the Diagnostic and Statistical Manual for Mental Disorders. However, many of the included studies are based on samples of adolescents or college students, where these behaviours might be more frequent than in other age groups [27] . This age bias might have produced this apparent similarity.…”
Section: 9)]mentioning
confidence: 99%
“…These elements are reminiscent of those defined as criteria for certain personality disorders (such as borderline or antisocial personality disorder) in the 4th edition of the Diagnostic and Statistical Manual for Mental Disorders. However, many of the included studies are based on samples of adolescents or college students, where these behaviours might be more frequent than in other age groups [27] . This age bias might have produced this apparent similarity.…”
Section: 9)]mentioning
confidence: 99%
“…Two relevant studies have reported prevalence rates of BPD in high school samples. One reported a rate of 6%, and the other 14% (Chabrol, Montovany, Chouicha, Callahan, & Mullet, 2001;Chabrol et al, 2004). It should be noted, however, that the prevalence of BPD was measured by a self-report questionnaire, which may have overestimated the frequency of personality disorders (Emmelkamp & Kamphuis, 2007).…”
Section: Introductionmentioning
confidence: 98%
“…Plus particulièrement, la prévalence du TPL chez les adolescents serait relativement élevée. Les études épidémiologiques en population générale révèlent qu'entre 6 et 14 % des adolescents présenteraient ce trouble avec des taux plus élevés autour de l'âge de 13 ans ainsi qu'à la fin de l'adolescence (Bernstein et al, 1993;Chabrol, Chouicha, Montovany, & Callahan, 2001;Chabrol, Chouicha, Montovany, Duconge, Callahan, & Mullet, 2003). Une proportion non négligeable d'adolescents suivis en psychiatrie présente un trouble de la personnalité.…”
Section: Selon La Dernière Version Du Diagnostic and Statistical Manuunclassified